A Role Discovered: Exploring Northwell Health's Patient Experience Structure and Leadership Characteristics - Agnes Barden; Nicole Giammarinaro; Natalie Rousseau; Carolyne Burgess (Patient Experience Journal)
Examining the evolution of healthcare, leaders in patient experience (PX) have played a pivotal role in shaping a more compassionate and human-centered landscape. This three-part multi-modal descriptive study aimed to investigate shared traits, skills, and characteristics among PX leaders in hospital settings. Employing a transformational leadership self-assessment tool and a guided interview process, recurring themes surfaced. The majority of participants reported employing a transformational leadership style. PX leaders emphasized the significance of communication, empathy, adaptability, teamwork, presence, and relationship-building in their roles. While hospital executive leaders had a slightly varied perspective on essential PX leader skillsets, they underscored the importance of analysis, execution, and collaboration. As the role of PX leaders continues to evolve, an understanding and awareness of these behavioral competencies can aid in the identification, development, and retention of PX talent.